Identification of sandflies(Diptera: Psychodidae: Phlebotominae) blood meals ins an endemic leishmaniasis area in Brazil - TANURE, Aline; PEIXOTO, Jennifer Cunha; AFONSO, Margarete Martins dos Santos; DUARTE, Rosemere; PINHEIRO, Aimara da Costa; COELHO, Suedali Villas Bôas; BARATA, Ricardo Andrade (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
The aim of this study was to identify blood meals of female sandflies captured in the municipality of Governador Valadares, an endemic area of visceral and cutaneous leishmaniasis, in the State of Minas Gerais, Brazil. From May 2011 to January 2012, captures were performed using HP light traps in four districts. There were 2,614 specimens (2,090 males and 524 females) captured; 97 engorged females were identified belonging to the species Lutzomyia longipalpis(82.1%) and Lutzomyia cortelezzii(17.9%). Considering simple and mixed feeding, the enzyme-linked immunosorbent assay revealed a predominance of chicken blood (43.6%) in Lutzomyia longipalpis, showing the important role that chickens exert around the residential areas of Governador Valadares. This finding increases the chances of sandflies contact with other vertebrates and consequently the risk of leishmaniasis transmission.